Pengaruh Cairan Alkali Terhadap Kuat Geser, Kuat Tekan Bebas Dan Konsistensi Pada Tanah Lempung - Risal, Risal; Sariman, Syahrul; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Clay soil is an aggregate of microscopic and submicroscopic particles derived from the chemical decay of the constituent elements of the aid. One of the efforts to improve clay soil by adding alkaline liquid as a soil stabilization agent by testing shear strength and free compressive strength and consistency. This study used the addition of alkaline liquid as much as 0.8%, 1%, 1.2%, and 1.4% of the weight of dry soil. From the results of the study, the highest value of shear strength testing, cohesion value and shear angle was obtained at the addition of 1.4% alkaline liquid, namely 0.5280 value of shear strength, 0.38540 for cohesion value and 27.83 value of shear angle. In the compressive strength test, the highest increase occurred in 1.4% alkaline liquid, which is 0.864. Similarly, in the consistency test, the highest increase was obtained in the addition of alkaline liquid 1.4%, in the liquid limit test the highest value was 56.93, the plastic limit was 29.07, the shrinkage limit was 19.62 and the plasticity index value was 27.86. It can be concluded that the test results of shear strength obtained an increase in the value of cohesion, shear strength and soil shear angle at the addition of 1.4%, in the liquid limit test the highest value was 56.93, the plastic limit was 29.07, the shrinkage limit was 19.62 and the plasticity index value was 27.86.